PENGARUH HARGA DAN PROMOSI TERHADAP MINAT BELI JEANS UNIQLO DI DELI PARK MALL MEDAN - Hartina Simatupang; Nur’ain Harahap (Universitas Dharmawangsa, 2022)
This study aims to determine whether there is an influence between price and promotion on buying interest. In this study, the authors use descriptive and quantitative analysis with a sample of 100 consumers who shop for Uniqlo Jeans at Deli Park Mall Medan. This research was conducted by distributing questionnaires to Uniqlo Jeans consumers in Deli Park Medan. The results showed that price and promotion had an influence on buying interest in Uniqlo Jeans at Deli Park Mall Medan as indicated by the results of multiple regression Y = 7,733+ 0,420X1 + 0,375X2 + e. In the results of the partial test (t test) of price on buying interest, the value of tcount = 4.133>1.66 and the value of the partial test (t-test) of promotion obtained a value of tcount = 4.083>1.66, this shows that partially price and promotion have an effect positive and significant on buying interest in Uniqlo Jeans at Deli Park Mall Medan, besides the F test results obtained Fcount>Ftable (98,767>3,090) with a probability level (0.01<0.05). The value of the coefficient of determination (R2) of 0.671 means that price and promotion can increase buying interest in Uniqlo Jeans at Deli Park Mall Medan by 67,1% and the remaining 32,9% is explained by other variables outside the study.